Amalan pengajaran berkualiti guru prasekolah: kajian kes di prasekolah KPM Sabah - Jadira C. Joannes Ajuni (Tanjong Malim, 2019)
Amalan pengajaran berkualiti guru prasekolah: kajian kes di prasekolah KPM Sabah by Jadira C. Joannes Ajuni